The Middle Included Logos in Aristotle - Aygün, Ömer (Rereading Ancient Philosophy, 2016)
The Middle Included is a systematic exploration of the meanings of logos throughout Aristotle's work. It claims that the basic meaning is "gathering," a relation that holds its terms together without isolating them or collapsing one to the other. This meaning also applies to logos in the sense of human language. Aristotle describes how some animals are capable of understanding non-firsthand experience without being able to relay it, while others relay it without understanding. Aygün argues that what distinguishes human language, for Aristotle, is its ability to both understand and relay firsthand and non-firsthand experiences. This ability is key to understanding the human condition: science, history, news media, propaganda, gossip, utopian fiction, and sophistry, as well as philosophy. Ömer Aygün finds Aristotle's name for this peculiar but crucial human ability of "gathering" both experiences is logos, and this leads to a claim about the specificity of human rationality and language.